Emotions of fear and disgust: subjective and cardiac responses as a function of different sensory stimuli - Ferreira, Jacqueline Helena Tavares (2021)
The work presented in this thesis aimed to explored the cardiac response of the emotions of disgust and fear using visuo-auditory and olfactory stimuli. This thesis is organized into three major sections. The first section provides a brief revision of the theories of emotions, a brief description of automatic recognition of emotion based on ECG (electrocardiogram) and a review of chemosensory signals transmitted via body odors, as well as their effects in human’s physiological, cognitive and behavioral responses. The second section presents the four studies that were conducted. In Study 1we used movies to induce disgust, fear and neutral emotions and examined whether noise entropy of ECG can work as a potential biomarker to discriminate disgust from fear and neutral conditions. The results showed that it is possible to discriminate such emotions based on ECG noise entropy with 88% (p<.05) accuracy and that the median value of the disgust condition was higher when compared with the fear and neutral conditions. In Study 2 we developed and tested a classifier to automatically classify emotions using noise entropy of ECG. The performance of the classifier was good for fear and disgust identification (60% of sensitivity and 80% of specificity) and perfect for identification of the neutral condition (100%). In addition to the responses to the visual stimuli, we also evaluated the cardiac response using olfactory stimuli, namely the body odors collected in conditions of disgust, fear and neutral. To control for potential individual differences in disgust propensity and sensitivity on body odor perception, in Study 3 we examined the psychometric properties of the Portuguese version of DPSS-R. The results confirmed the existence of two distinct factors, disgust propensity and sensitivity. Moreover, the scale showed an acceptable convergent and discriminant validity and a satisfactory reliability. In the Study 4 we investigated how a BO prime affects the emotional tone of a subsequent BO message, on cardiac and subjective responses. The results demonstrated a reduction in heart rate variability (HRV-HF) when the participants smelled the neutral body odors after they smelled the disgust and fear body odors. The effect of order of presentation was also evident in the subjective ratings, with the neutral odors being perceived as more intense when the receivers smelled the neutral odors after they smelled the negative body odors. Such effects were independent of the pleasantness of the body odors. Finally, in the third section we presented the general discussion of the main results, the current limitations of the studies as well the future directions and the potential implications and applications of the results. Overall, the findings of the studies described in this thesis suggest that the ECG noise contains meaningful information that can allow emotion recognition and that the order of presentation of body odor can affect the cardiac response and subjective response of the receivers.